Predictors of long-term mortality among perioperative survivors of Fontan operation. (9th December 2021) - Inai, Kei; Inuzuka, Ryo; Ono, Hiroshi; Nii, Masaki; Ohtsuki, Shinichi; Kurita, Yoshihiko; Takeda, Atsuhito; Hirono, Keiichi; Takei, Kohta; Yasukouchi, Satoshi; Yoshikawa, Tadahiro; Furutani, Yoshiyuki; et al.
Abstract: Aims: The criteria for 'good' Fontan haemodynamics have been poorly defined in relation to long-term outcomes. The aim of this study was to identify the risk factors for mortality among haemodynamic parameters obtained early after the Fontan operation. Methods and results: Clinical data of all perioperative survivors of the Fontan operation performed before 2011, from nine institutions, were collected through a retrospective chart review. In total, 1260 patients were included. The median age at the time of Fontan operation was 3.6 years. Post-operative cardiac catheterization was conducted in 1117 patients at a median period of 1.0 years after the operation. During the median follow-up period of 10.2 years, 107 patients died. The mortality rates at 10, 20, and 25 years after the operation were 5%, 12%, and 22%, respectively. On multivariable analysis, older age at the time of the operation ≥15 years, hazard ratio (HR) [95% confidence interval (CI)]: 3.2 (1.7–5.9) and haemodynamic parameters obtained at post-operative catheterization, such as low ejection fraction [<30%, HR (95% CI): 7.5 (3.2–18)], low systemic oxygen saturation [<80%, HR (95% CI): 3.8 (1.6–9.1)], high central venous pressure [≥16 mmHg, HR (95% CI): 2.3 (1.3–3.9)], and low mean systemic arterial pressure [<60 mmHg, HR (95% CI): 3.0 (1.4–6.2)] were identified as independent predictors of mortality. The predictive model based on these parameters had a c-index of 0.75 at 10 years. Conclusions: Haemodynamic parameters obtained at a median period of 1.0 years, post-operatively, can accurately identify patients with a high mortality risk, who may need intensive management to improve long-term outcomes. Structured Graphical Abstract: